Literature review on linkages between child nutrition and economic growth - Haile, Beliyou; Azzarri, Carlo; Ahn, Hee Eun (International Food Policy Research Institute, 2021)
This document summarizes published and grey literature on conceptual framework on the link between child nutrition and economic growth, determinants of child undernutrition, types of investments to enhance maternal and child nutrition, and linkages between urbanization and child nutrition. Several in-sights emerge from the review. First, and despite progresses over the last several decades, maternal and child malnutrition is still prevalent in developing countries and the progress has been uneven. While the percentage of chronically malnourished (stunted) children declined across the developing world, the number of stunted children in Africa increased due to slower reduction in stunting prevalence and population growth. Many developing countries are experiencing the coexistence of different forms of malnutrition including undernutrition, micronutrient deficiency, and overnutrition. Second, child undernutrition, especially stunting during the first 1,000 days of life, has several short- and long-term effects on individuals and economies that include impaired cognitive and non-cognitive development, poor educational performance, low productivity and earnings, and higher healthcare costs. Third, the determinants of child undernutrition are broadly classified as the immediate determinants including dietary intake and diseases; the underlying determinants that include household food security, quality of care and household living environment, and access to healthcare; and the basic determinants that include access to productive resources, stock of capital, as well as socioeconomic, political and cultural factors. Investments to enhance child nutrition can target either the immediate determinants (known as nutrition-specific investments) or the underlying determinants (known as nutrition-sensitive investments). Fourth, the effect of urbanization on child nutrition is mostly determined by the extent to which urban settlements offer their residents with better economic opportunities (e.g., better paying jobs and markets for nutritious food) and services (e.g., healthier living environments). Fifth, given the multilayer causes of child undernutrition, a multi-sectoral approach is needed to address the various determinants of undernutrition to improve maternal nutrition, promote optimal infant and young child feeding practices, enhance household food security, as well as improve healthy living environment and access to quality health care.